2017
DOI: 10.1021/acs.jpcc.7b03779
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Probe-Molecule, Mössbauer, Nuclear Resonance Vibrational Spectroscopy, and Density Functional Theory Approach for Evaluation of Potential Iron Active Sites in an Oxygen Reduction Reaction Catalyst

Abstract: Nonprecious metal M−N−C (M = Fe or Co) catalysts that are effective for the oxygen-reduction reaction in polymerelectrolyte fuel cells have been developed, but no consensus has yet been reached regarding the nature of the M sites in these heterogeneous catalysts that are responsible for the reaction with dioxygen (O 2 ). While multiple studies have developed correlations between Fe distributions in as-prepared catalysts and ORR activity, the direct identification of sites reactive toward O 2 or O 2 -analogue m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 57 publications
5
56
1
Order By: Relevance
“…The modes between 250 cm −1 and 380 cm −1 are assigned to Fe−N pyr . A very dominant feature around 381 cm −1 and 395 cm −1 can be seen, which was not found by Kneebone et al . for their PANI‐based catalyst in any of the investigated states (reduced or NO‐treated).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The modes between 250 cm −1 and 380 cm −1 are assigned to Fe−N pyr . A very dominant feature around 381 cm −1 and 395 cm −1 can be seen, which was not found by Kneebone et al . for their PANI‐based catalyst in any of the investigated states (reduced or NO‐treated).…”
Section: Resultscontrasting
confidence: 54%
“…Kneebone et al . used Mössbauer spectroscopy at 80 K and nuclear inelastic scattering (NIS) to characterize a PANI‐based Fe–N–C catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…g . different ORR activities and Fe 2+/3+ redox potentials (Figure d)), and iii) electrochemical perturbation of FeN x C y moieties during reduction reaction require additional studies to address the reversible/irreversible Fe sites more clearly. We believe that the in situ observation of two different electrochemical behaviors of atomic FeN x C y sites is however still meaningful, and potentially guides rational design of next‐generation Fe−N−C catalysts.…”
Section: Discussionmentioning
confidence: 99%
“…9 Besides, physical methods such as neutron activation and Mössbauer spectroscopy were also used to identify the possible ORR active centers in an Fe/N-C catalyst. [10][11][12][13] Recently, low temperature pulse CO chemisorption was applied to estimate the active site density of NPMCs, assuming the metal as the only ORR active center. 14 It was reported that, even at low temperatures (193 AE 5 K), CO does not adsorb on the nitrogen center of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…In another report, NO (g) was used as the probe molecule to detect the iron center in Fe/N-C catalyst. 13 Thus, development of an electrochemical method to estimate the active site density of metal-free carbon and nitrogen-doped carbon is paramount.…”
Section: Introductionmentioning
confidence: 99%